Deep Gray Matter Iron Content in Neuromyelitis Optica and Multiple Sclerosis. (19th May 2020) - Pudlac, Adam; Burgetova, Andrea; Dusek, Petr; Nytrova, Petra; Vaneckova, Manuela; Horakova, Dana; Krasensky, Jan; Lambert, Lukas
Abstract : Background . Neuromyelitis optica (NMO) and multiple sclerosis (MS) are often presenting with overlapping symptoms. The aim of this study was to determine whether and how NMO and MS differ regarding cerebral iron deposits in deep gray matter (DGM) and the correlation between iron deposition and clinical severity as well as to regional atrophy of the DGM. Methods . We analyzed 20 patients with NMO, 40 patients with a relapsing-remitting (RR) form of MS, and 20 healthy controls with 1.5T MRI. Quantitative susceptibility mapping (QSM) was performed to estimate iron concentration in the DGM. Results . Patients with NMO have higher magnetic susceptibility values in the substantia nigra compared to healthy controls. RRMS patients have lower magnetic susceptibility values in the thalamus compared to healthy controls and NMO patients. Atrophy of the thalamus, pulvinar, and putamen is significant both in RRMS compared to NMO patients and healthy controls. A correlation was found between the disability score (EDSS) and magnetic susceptibility in the putamen in RRMS. Conclusions . This study confirms that a disturbed cerebral iron homeostasis in patients with NMO occurs in different structures than in patients with RRMS. Increased magnetic susceptibility in substantia nigra in NMO and decreased magnetic susceptibility within the thalamus in RRMS were the only significant differences in the study sample. We could confirm that iron concentration in the thalami is decreased in RRMS compared to that in the HC group. Positive association was found between putaminal iron and EDSS in RRMS.